South Eastern Regional Library & Information Network (SERLIN) of Sri Lanka - Mashroofa, M.M.; Rifaudeen, M.M.; Azwer, M.C.M.; Nahfees, A.M.; Sajeer, S.L.M.; Saajith, M.J. (Library, University of Jaffna, 2024)
South Eastern University of Sri Lanka (SEUSL) is located in the Ampara district in which the public, school, and college libraries function with poor infrastructure, human resources, and information sources. The libraries of SEUSL are fully fledged libraries with enriched collections of print and electronic resources, modern information services, space, professionally qualified library academics/ professionals, paraprofessionals, a digital library, an Online Public Access Catalogue (OPAC), and automated Library Management ystem. AsS a community outreach, SEUSL libraries extended their services to the libraries across the Ampara district by establishing a Library & Information Network under the umbrella of SEUSL libraries. This network has been named as “South Eastern Regional Library & Information Network (SERLIN) of Sri Lanka”. According to Chatterjee (2016), “Information /Library Networks refer to collaborative systems developed by the cooperation of multiple libraries or information centers. These networks can be local (LAN) or wide area (WAN), connecting institutions within a small or large geographical area respectively, to pool resources and provide access to a wider range of information sources”. The main objective of this project is to bring all the libraries in Ampara district to a common platform to share the available resources, expertise and services among members of the network.
Keywords: SERLIN network; SEUSL; Information services